Pentingnya Web Desa Berbasis Kemitraan Desa Oluhuta Menuju Desa Mandiri - Lukman Pakaya (BADAN PENERBIT STIEPARI PRESS, 2023)
This partnership-based community service activity lasted for 4 months as a form of independent learning internship at the MBKM independent campus. By carrying out the program on the importance of the village website for villages in the Kabila Bone sub-district, Bone Bolango district, the service team realized the Oluhuta village website creation program, where this village is located in the Tomini Bay area of Gorontalo province. The purpose of making the Oluhuta village website is not just to introduce Oluhuta village to the public, but also to gather information about villages with village potential.